An Exciting Cinematic Year - Yow, Chong Lee (2015)
2014 observed one of the most exciting cinematic scenes locally and internationally. Many international (award winning) films had been brought into Malaysia and screened at our local theatres, mainly through film festivals which strive to offer an alternative film culture to Malaysian audiences.